Genetic and ecological variability of Stylosanthes macrocephala determined by RAPD markers and GIS - Barros, Ana Maria; Faleiro, Fábio Gelape; Karia, Cláudio Takao; Shiratsuchi, Luciano Shozo; de Andrade, Ronaldo Pereira; Lopes, George Kihoma Britto (Pesquisa Agropecuaria Brasileira, 2005)
Stylosanthes macrocephala M. B. Ferr et S. Costa is a leguminous species used as forage, cover crop and as a pioneer plant to recover degraded areas. Inexistence of stable morphological descriptors and lack of ecogeographic information about collecting sites bring difficulties to the studies of this species. The objective of this work was to use the geographic information system (GIS) and RAPD markers to obtain ecological and molecular descriptors and to study the genetic variability of 87 S. macrocephala accessions. The accessions were collected from different ecogeographical areas in seven Brazilian States, five hydrographic regions, seven vegetation types and seven soil types. Collecting sites ranged from 1 to 1,298 m above sea level with annual rainfall from 550 to 2,870 mm. Accession distribution along those diverse ecosystems indicate high adaptive diversity. Using 161 RAPD markers, genetic distances between accessions ranged from 0.02 to 0.42. These genetic distances allowed the establishment of ten genetic groups. Accessions collected in specific hydrographic region tended to be grouped in the same genetic group. Accessions collected in Bahia and Minas Gerais States showed high genetic variability. The high genetic variability observed in the accessions showed the importance of this S. macrocephala collection for breeding programs.